2017
DOI: 10.7554/elife.20898
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic outcomes in Mouse and Human Foxc1 dependent Dandy-Walker cerebellar malformation suggest shared mechanisms

Abstract: FOXC1 loss contributes to Dandy-Walker malformation (DWM), a common human cerebellar malformation. Previously, we found that complete Foxc1 loss leads to aberrations in proliferation, neuronal differentiation and migration in the embryonic mouse cerebellum (Haldipur et al., 2014). We now demonstrate that hypomorphic Foxc1 mutant mice have granule and Purkinje cell abnormalities causing subsequent disruptions in postnatal cerebellar foliation and lamination. Particularly striking is the presence of a partially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 26 publications
(62 reference statements)
3
33
0
Order By: Relevance
“…The diversity of FOXC1 mutations is thought to account for the range of clinical manifestations of ARS [26,27,28]. More recently, FOXC1 mutations were linked to Dandy-Walker syndrome, a group of disorders characterized by cerebellar defects and a variable set of craniofacial, cardiac and limb abnormalities [29,30]. Another report found that FOXC1 mutations were also associated with diverse microvascular abnormalities in the brain consistent with cerebral small vessel disease [31].…”
Section: Foxc1 In Tissue Development Homeostasis and Diseasementioning
confidence: 99%
“…The diversity of FOXC1 mutations is thought to account for the range of clinical manifestations of ARS [26,27,28]. More recently, FOXC1 mutations were linked to Dandy-Walker syndrome, a group of disorders characterized by cerebellar defects and a variable set of craniofacial, cardiac and limb abnormalities [29,30]. Another report found that FOXC1 mutations were also associated with diverse microvascular abnormalities in the brain consistent with cerebral small vessel disease [31].…”
Section: Foxc1 In Tissue Development Homeostasis and Diseasementioning
confidence: 99%
“…Moreover, this mode of spatial patterning is conserved, as a similar partitioning was recently reported in zebrafish 41 . It could be that defects in these early compartmental events are responsible for the region-specific abnormalities in cerebellar foliation and layering in Dandy–Walker malformation 42 . This is not the only level of compartmental organization in granule cells.…”
Section: Granule Cells Are Critical For Postnatal Morphogenesismentioning
confidence: 99%
“…This refined algorithm gives us a data-driven model of the features within the dataset that contribute to the final classification, providing further insight into the structural morphology associated with the classification criteria and underlying pathology. We chose the cerebellum as the test substructure to test our algorithm because: (1) its relatively simple structure to segment compared to other regions of the brain, including the cerebral cortex and other subcortical structures including the hippocampus; (2) there are known neuroradiological criteria for cerebellar dysplasia in the developing human infant; 1416 and (3) anatomic related-sub regions of the developing cerebellum are important mediators of both genetics factors, 17,18 and downstream pathways associated with neurodevelopmental impairment. 19,20 We tested our algorithm on a dataset of term neonates born with CHD at high risk for brain dysmaturation, including recently described cerebellar abnormalities, including both hypoplasia and dysplasia.…”
Section: Introductionmentioning
confidence: 99%